The Role of Protein S-Nitrosylation in Protein Misfolding-Associated Diseases - Yun-Jin Ju; Hye-Won Lee; Ji-Woong Choi; Min-Sik Choi (Life, 2021)
Abnormal and excessive nitrosative stress contributes to neurodegenerative disease associated with the production of pathological levels of misfolded proteins. The accumulated findings strongly suggest that excessive NO production can induce and deepen these pathological processes, particularly by the S-nitrosylation of target proteins. Therefore, the relationship between S-nitrosylated proteins and the accumulation of misfolded proteins was reviewed. We particularly focused on the S-nitrosylation of E3-ubiquitin-protein ligase, parkin, and endoplasmic reticulum chaperone, PDI, which contribute to the accumulation of misfolded proteins. In addition to the target proteins being S-nitrosylated, NOS, which produces NO, and GSNOR, which inhibits S-nitrosylation, were also suggested as potential therapeutic targets for protein misfolding-associated diseases.